2004
DOI: 10.1007/s00192-004-1215-z
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle fraction of the round ligament in women with pelvic organ prolapse: a computer-based morphometric analysis

Abstract: Our objective was to compare the collagen and muscle content of the round ligament of uteri in women with pelvic organ prolapse. We evaluated the tissue samples obtained from the round ligaments of 22 patients with uterine prolapse who underwent vaginal hysterectomy (group A, study) and from 26 patients with no pelvic relaxation in whom total abdominal hysterectomy was performed for benign reasons (group B, controls). Morphometric analysis was performed on histologic cross-sections of the round ligament. Secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 20 publications
(19 reference statements)
2
24
1
Order By: Relevance
“…In the round ligament, a significantly decreased smooth muscle fraction was morphometrically measured in H&E and Masson's trichrome slides from women with uterine prolapse. 22 In parallel with the Ozdegirmenci et al study, 22 we showed that the mean smooth muscle percentage in the round ligament of the women with prolapse was significantly lower than in women with normal support. In addition to their study, we evaluated the muscle content by immunohistochemically by SMA and we also investigated the smooth muscle percentage of the uterosacral and cardinal ligaments of the uterus.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…In the round ligament, a significantly decreased smooth muscle fraction was morphometrically measured in H&E and Masson's trichrome slides from women with uterine prolapse. 22 In parallel with the Ozdegirmenci et al study, 22 we showed that the mean smooth muscle percentage in the round ligament of the women with prolapse was significantly lower than in women with normal support. In addition to their study, we evaluated the muscle content by immunohistochemically by SMA and we also investigated the smooth muscle percentage of the uterosacral and cardinal ligaments of the uterus.…”
supporting
confidence: 76%
“…4,29,30 Zhu et al study 5 demonstrated no correlation between nerve fiber profiles and parity in SUI, POP, and control subjects. Contrary to this finding, Ozdegirmenci et al 22 have found a negative correlation between parity and smooth muscle content of the ligament in the study group. Our study showed that neuromuscular changes of the tissues are directly related to the parity, age and number of vaginal deliveries.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…By morphometry of SMA immunostained areas in sections from the anterior vaginal apex, a significant reduction in smooth muscle cell content in women with POP compared to a control group was described [30]. In the round ligament, a significantly decreased smooth muscle fraction was morphometrically measured in H&E and Masson's trichrome slides from women with uterine prolapse [31]. In contrast, Gabriel et al [13] observed no difference in the fraction of smooth muscle in USL in postmenopausal women with or without POP.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that abnormalities of the connective tissue composition may contribute to the genesis of POP [8][9][10].…”
Section: Introductionmentioning
confidence: 99%